2022
DOI: 10.1039/d1an02290c
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in small-molecule fluorescent probes for endoplasmic reticulum imaging in biological systems

Abstract: Endoplasmic reticulum (ER) is the indispensable organelle in eukaryotic cells involving in proteins synthesizing, processing, as well as calcium storage and release. The maintaining of ER quality is of great...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 143 publications
(139 reference statements)
0
10
0
Order By: Relevance
“…It can be found that the fluorescence signal of ERC in the red channel overlapped well with that of ER-Tracker Green (Figure a–d), and the Pearson’s correlation coefficient was defined as high as 0.88, implying the potent ER-targeting capacity of ERC . This hinted that the hydrophobicity of the ERC molecule allowed it to readily partition into the ER membrane environment . Meanwhile, the same subcellular distribution of ERP was fully verified in HepG2 cells with a commercial ER dye, ER-Tracker Red, in which the Pearson’s correlation coefficient was determined as 0.91 (Figure e–h).…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…It can be found that the fluorescence signal of ERC in the red channel overlapped well with that of ER-Tracker Green (Figure a–d), and the Pearson’s correlation coefficient was defined as high as 0.88, implying the potent ER-targeting capacity of ERC . This hinted that the hydrophobicity of the ERC molecule allowed it to readily partition into the ER membrane environment . Meanwhile, the same subcellular distribution of ERP was fully verified in HepG2 cells with a commercial ER dye, ER-Tracker Red, in which the Pearson’s correlation coefficient was determined as 0.91 (Figure e–h).…”
Section: Resultsmentioning
confidence: 64%
“…This hinted that the hydrophobicity of the ERC molecule allowed it to readily partition into the ER membrane environment. 35 Meanwhile, the same subcellular distribution of ERP was fully verified in HepG2 cells with a commercial ER dye, ER-Tracker Red, in which the Pearson's correlation coefficient was determined as 0.91 (Figure 3e−h).…”
Section: ■ Results and Discussionmentioning
confidence: 71%
“…13 Moreover, ρ -toluenesulfonamide was a recognized ER-targeting group. 27 In this study, these three compounds were combined to develop a novel fluorescent probe, ER-NE (Fig. S1–S3, ESI†).…”
Section: Resultsmentioning
confidence: 99%
“…GJ can be observed in electrical synapses (representing a minority of interneural connections in mammals) and seem to play a particular role in astrocytes, where they allow the coupling of astrocytes to each other to form networks [ 40 , 41 ] in which cells can exchange signals mediated by calcium waves [ 42 ]. In the last decades, this process was widely visualized and monitored in vitro by using fluorescent calcium indicators and quantitative microscopy techniques [ 43 , 44 , 45 ]. Tools for studying Ca 2+ dynamics in vivo have also been developed [ 46 ], allowing for simultaneous image astrocyte calcium activity alongside astrocyte-specific perturbations (see [ 47 ]).…”
Section: Intercellular Communication In the Cnsmentioning
confidence: 99%